Effect of Citizens’ Participation on the Performance of Gravity Water Scheme in Kaharo Sub-County Kabale District. - Ahimbisibwe, Sonia (Kabale University, 2024)
The study, titled "Effect of Citizens’ Participation on the Performance of Gravity Water Scheme in Kaharo Sub-County, Kabale District," examines the influence of citizen involvement on the operational efficiency and sustainability of gravity water schemes. It is guided by three specific objectives: to assess the forms of citizen participation employed in gravity water schemes, to determine how citizen involvement impacts the operational performance of these schemes, and to identify the barriers to effective participation. A mixed-methods research approach was used, integrating quantitative surveys and qualitative interviews to collect data from community members, Water User Committee (WUC) members, and local officials. The quantitative aspect involved structured surveys administered to 80 respondents, while the qualitative component consisted of in-depth interviews with key informants. The findings indicate that the main forms of citizen participation in gravity water schemes include consultation and feedback (62.5%), involvement in implementation (45.0%), management and maintenance by WUC members (40.0%), and participation in decision-making (35.0%). The study also found that citizen participation positively influences the operational performance of the water schemes, with 57.5% of respondents reporting improved system reliability and reduced downtime due to community involvement. However, 42.5% noted challenges such as inconsistent engagement and inadequate maintenance practices. Key barriers to effective participation include limited local capacity (54.0%), political interference (48.0%), unequal representation in decision-making (45.0%), and resource constraints (42.5%). The study recommends enhancing capacity-building initiatives to develop local water management skills, mitigating political interference through transparent governance, and providing increased financial and technical support to sustain the schemes. Strengthening the role of WUCs and encouraging inclusive participation are also critical for improving the performance of gravity water schemes in Kaharo Sub-County.